Treatment for Clubfoot: Stockinette Versus Webril Cast Padding in the Ponseti Method. Issue 10 (November 2020) - Marien, Meaghan; Abouassaly, Marcel; Jarvis, James; Smit, Kevin; Kontio, Ken
Abstract : Background: The Ponseti method of serial manipulation and casting revolutionized the treatment of one of the most common congenital orthopaedic conditions—clubfoot—resulting in less surgical morbidity and better functional results. Several studies have examined aspects of nonoperative treatment but none have explored the effect of different types of undercast padding. Methods: The authors performed a randomized controlled trial comparing cotton Stockinette and Webril undercast padding using the Ponseti method. They included 56 patients under the age of 6 months who had an untreated idiopathic clubfoot. For treatment, the padding was randomized to double-layer Stockinette (29 patients) or standard 2- to 3-layer Webril (27 patients). The primary analysis consisted of a 2-sample t test comparing the mean number of casts required for correction in each group. Secondary outcomes included initial and final standardized clubfoot scores (Pirani and Dimeglio scores) and adverse events. Results: Baseline demographics were not statistically different between groups, with respect to mean age, sex, and side being treated, nor were the baseline Dimeglio and Pirani scores. The primary outcome analysis revealed an equivalent number of casts (about 4) required before tenotomy. The secondary analysis on complications did not show any significant difference, with 10 events documented in the Webril group and 9 in the Stockinette group ( P =1.00). At the end of the study, the mean Dimeglio (3.9±2.1 vs. 3.9±1.8, P =0.99) and Pirani (2.1±0.8 vs. 2.2±0.8, P =0.70) scores were not significantly different. Subjectively, parents and doctors indicated a substantially more positive experience for the Stockinette group. Conclusions: Webril and Stockinette paddings provide equivalent clubfoot deformity correction while applying a similar number of casts before tenotomy. Although minor skin complications were observed, these were not significantly different between groups.